Predictive impact of rare genomic copy number variations in siblings of individuals with autism spectrum disorders - L. D’Abate (Nature Portfolio, 2019)
Siblings of those with autism spectrum disorder (ASD) have increased likelihood of ASD or related subclinical traits. Here, studying 253 ASD families, D’Abate et al. test the predictive value of genomic copy number variation involving ASD-associated loci, with confirmation in a second cohort.